A sub-regional innovation ecosystem? Life sciences and health in the Swansea Bay City Region. (2018) - Davies, Gareth Huw; Roderick, Sian; Williams, Mike
This paper presents the case of 'AgorIP', a novel technology transfer approach to support knowledge-based regional economic development in the post-industrial region of Southwest Wales in the UK, centred upon an entrepreneurial learning university applying smart specialisation in a regional innovation system (RIS). In this context, West Wales and the Valleys have been working to develop a nascent life sciences and health cluster through efforts of the private sector, health service, academia and government. A central part of this agenda is driving technology transfer within the Swansea Bay City Region. The associated internet coast city deal combines efforts of the UK, Welsh and local governments together with wider partners to exploit identified strengths in life sciences and health. Through analysis of regional sector survey data and case study review of key regional initiatives, this paper examines the opportunities and challenges for the region to flourish in uncertain changing times.